Pengaruh Latihan Resistance Bands Terhadap Kecepatan Pukulan Gyaku-Tsuki Pada Atlet Karate Dojo Forki Surakarta - Sukman, Muhammad Rafif; Subekti, Nur; Syaukani, Agam Akhmad (Center for Sports Science , Faculty of Sport Science, Universitas Negeri Padang, 2026)
This study aimed to investigate the effects of resistance band training on the execution speed of the gyaku-tsuki strike among karate athletes from the FORKI Dojo in Surakarta. A quantitative approach was adopted, employing a quasi-experimental design in the form of a one-group pretest-posttest study. The sample population consisted of 13 athletes recruited as the main participants. The intervention was carried out through a resistance band training programme over six weeks, with three sessions per week. Data were measured via gyaku-tsuki punch speed tests at the initial (pre-test) and final (post-test) stages. Descriptive analysis indicated a pre-test mean of 44.31 (standard deviation 5.808), which subsequently increased to 71.00 (standard deviation 8.593) at the post-test. A hypothesis test using a paired sample t-test yielded a significance value of 0.000 (<0.05), concluding that there is a significant effect of resistance band training on the improvement of gyaku-tsuki strike speed. Therefore, resistance band training is recommended as an effective supplementary training strategy to optimise the striking performance of karate athletes.